P2_7 Outrunning Climate Change - O'Sullivan, Rachael; Carter, Samuel; Lyons, Hannah; Nixon, Josh (Physics Special Topics, 2022)
In this paper we investigate the rate at which you would have to move Earth away from the Sun to combat the global temperature increase due to greenhouse gas emissions. By assuming the average global temperature increases linearly between 0.2 ◦C or 4.8 ◦C by the year 2100, we found that the Earth would need to be moved between 5.44 × 106 and 1.31 × 108 meters per year.